THE GROWTH OF COMPETITION IN THE INTERNATIONAL MARKET AND THE DYNAMIC DEVELOPMENT OF TRANSPORT ENTERPRISES - Yusupxodjaeva Gulchexra Baxadirxodjaevna (Scholar Express Journal, 2024)
This article is aimed at research and development of a unified digital transport and logistics intelligent platform based on the infrastructure of the national operator. Given the rapid development of the transport and logistics sector, the creation of this platform is an important strategic initiative.
Keywords: intelligent transport and logistics system; national operator; data integration